Analysis of Learning Media Needs for Aqidah Akhlak on the Asmaul Husana Material for Grade II Students at MI Al Hikmah Pujon - Silvia Khodrotun Nada; Indra Musthofa (Yayasan Rahmat Islamiyah, 2026)
The purpose of this study was to analyze the learning media needs for the Asmaul Husna material in the Akidah Akhlak subject. The research method used a qualitative approach with a case study type. This study was conducted at MI Al Hikmah, Pujon District, Malang Regency, East Java. Research results show that the teaching of akidah akhlak in the Asmaul Husna material in class II of MI Al Hikmah Pujon is not yet supported by learning media that suits the characteristics of the students. The conceptual nature of the Asmaul Husna material causes difficulties for students in memorizing and understanding its meaning, which affects their motivation and involvement in learning.